Fragment to framework: automatic fragmentation of covalent organic frameworks into building blocks for band gap analysis - Ernst, Michelle; Fedorov, Rostislav; Calzolari, Alessandro; Mollart, Catherine; Grieser, Fabian; Ber, Sophia; Gryn'ova, Ganna (Materials chemistry frontiers, 2026)
Understanding structure-property relationships in ordered functional materials is essential for their rational design and optimisation. Fragment-based approaches relating materials’ properties to those of their building blocks (fragments) are intuitive to chemistry and have been successfully applied in the design of metal-organic frameworks (MOFs). However, covalent organic frameworks (COFs) are resistant to such in silico fragmentation due to their covalent bonds and ambiguous definitions of nodes and linkers. Here we introduce a new algorithm, deCOFpose, designed to systematically fragment COFs into building blocks according to chemically intuitive rules, enabling fragment-based structure-property analysis, and exemplify the latter for COF band gaps. Our results reveal that the electronic features (e.g., energies of the frontier molecular orbitals) of the building blocks alone are insufficient to fully represent these materials, and the inclusion of their topological characteristics is required to engineer bespoke COFs with desired band structures.
Zuerst veröffentlicht: 26. November 2025
Gesehen am 27.02.2026